A Review of NAD(P)H:Quinone Oxidoreductase 1 (NQO1); A Multifunctional Antioxidant Enzyme - Ahmed Atia,Nadia Alrawaiq,Azman Abdullah (Journal of Applied Pharmaceutical Science, 2014)
NAD(P)H:quinone-oxidoreductase-1 (NQO1) is a cytosolic enzyme that catalyses two- or four-electron reduction of many endogenous and environmental quinones using flavin adenine dinucleotide (FAD) as a cofactor. It is a cytosolic enzyme exists as a homodimer and is biochemically distinguished by its prominent ability to use either NADH or NADPH as reducing cofactors and by its suppression by the anticoagulant dicumarol. This enzyme generally considered as a detoxification enzyme due to of its ability to diminish reactive quinones and quinone-imines to its less reactive and less toxic hydroquinones forms. NQO1 is a substantially inducible enzyme that is controlled by the Nrf2-Keap1/ARE pathway. Evidence for the significance of the antioxidant functions of NQO1 in suppression of oxidative stress is provided by manifestations that induction of NQO1 levels or their reduction are associated with reduced and raised susceptibilities to oxidative stress, respectively. The gene coding for NQO1 has two common polymorphisms at nucleotide position 609(C-T) and 465 (C-T) of the human cDNA. C465T causes reduction in enzyme activity, whereas the C609T results in complete loss of enzymatic activity due to protein instability.In this review, we discuss the protective functions of NQO1 and present its possible transcriptional pathways regulating its induction by Nrf2-Keap1/ARE pathway.
Keywords: NQO1,Nrf2,Keap1,ARE,SNP-Gene.